2021
DOI: 10.1177/0025802420934253
|View full text |Cite
|
Sign up to set email alerts
|

Dental age estimation: Demirjian’s versus the other methods in different populations. A literature review

Abstract: Age estimation is an important issue in forensic anthropology and odontology, since it is applied to both the living and the dead. Studies have shown that assessing tooth development using radiological methods is a reliable way to estimate age, especially in children. Demirjian’s method is the most widely used estimation method for dental age evaluation. Over the years, many methods have been developed in order to asses which one predicts more accurately the age. In the literature, many populations were examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 31 publications
0
20
0
4
Order By: Relevance
“…Los métodos basados en la maduración dental son ampliamente utilizados en contextos clínicos, odontológicos, forenses y antropológicos (De Donno et al, 2021), siendo el más empleado el propuesto por Demirjian & Goldstein (1976), mientras que en contextos de valoración deportiva su uso está menos extendido (Albaladejo-Saura et al, 2021;Beunen et al, 2006;Johnston et al, 2018;. Este método utiliza el desarrollo dental como indicador de la maduración biológica.…”
Section: Métodos Basados En Radiografías Dentalesunclassified
“…Los métodos basados en la maduración dental son ampliamente utilizados en contextos clínicos, odontológicos, forenses y antropológicos (De Donno et al, 2021), siendo el más empleado el propuesto por Demirjian & Goldstein (1976), mientras que en contextos de valoración deportiva su uso está menos extendido (Albaladejo-Saura et al, 2021;Beunen et al, 2006;Johnston et al, 2018;. Este método utiliza el desarrollo dental como indicador de la maduración biológica.…”
Section: Métodos Basados En Radiografías Dentalesunclassified
“…Age estimation represents one of the most important aspects of dental/skeletal analysis and forensic anthropology, playing a key role in human identification, both in living subjects and to establish identity in human remains 1 , 2 , 29 . This meta-analysis provides a comprehensive overview of the current literature on the validity of age estimation methods and reproducibility of maturity indices, in particular those based on dental maturation.…”
Section: Discussionmentioning
confidence: 99%
“…The Haavikko method had the highest variability, with a prediction interval ranging from − 6.88 to 4.65 for males and from − 7.24 to 4.57 for females. This might be due to the variability in dental maturation among subjects of different ethnic origin 1 , since Haavikko’s method is calibrated on Finnish children, whose dental maturation seems to occur earlier 68 . Recently, Butti et al 69 and Mohammed et al 50 reached the same conclusion that Haavikko’s method is unsuitable for both Italian and Indian children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of different researchers estimating dental age showed that there were some differences in the dental age between different regions and even the same region. Some researchers believed that the reason may be due to other environmental factors such as socio-economic conditions, nutrition and dietary habits, and lifestyle [5,11,12]. In Wang et al [5] Demirjian method underestimated chronological age, and the Willems method underestimated chronological age overall.…”
Section: Introductionmentioning
confidence: 99%